Interpersonal Communication between Parents and Children with Bullying Behavior in Students - Miftakhul Afif, Akhmad Khaidir; Hazim, Hazim (Universitas Muhammadiyah Metro, 2023)
This Study Was Conducted To Examine The Role Of Interpersonal Communication Between Parents And Children On Bullying Behavior In Students. The Research Method Used In This Study Is A Quantitative Approach. The Object Of Research Focuses On A Sample Of 51 Students And Uses Saturation Sampling Techniques. This Research Instrument Uses An Adaptation Scale With A Likert Model On Interpersonal Communication Between Parents And Children, Bullying Behavior. The Interpersonal Communication Scale Was Obtained From Issom & Damayanti With Cronbach's Alpha Reliability Of 0.964. The Bullying Behavior Scale Was Obtained From Putra With Cronbach's Alpha Reliability Of 0.891. Next, Data Analysis In This Research Uses Pearson's Product Moment Correlation. Research Results Conclude That There Is A Negative Relationship Between Interpersonal Communication Of Parents And Children With Bullying Behavior At Sm Muhammadiyah 4 Porong With A Value Of R = -0.395 With A Significance Value Of 0.004 (P < 0.05). Interpersonal Communication Between Parents And Children Contributes 15.6% To Bullying Behavior. So It Can Be Concluded That Interpersonal Communication Between Parents And Children Makes A Considerable Contribution In Influencing Bullying Behavior.